Publisher Correction: The diagnostic accuracy of circulating tumor DNA for the detection of EGFR-T790M mutation in NSCLC: a systematic review and meta-analysis. Issue 1 (December 2018) - Passiglia, Francesco; Rizzo, Sergio; Di Maio, Massimo; Galvano, Antonio; Badalamenti, Giuseppe; Listì, Angela; Gulotta, Leonardo; Castiglia, Marta; Fulfaro, Fabio; Bazan, Viviana; Russo, Antonio
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.